A STUDY TO EXPLORE THE CAUSES AND IMPACT OF STRESS AMONGST THE PUBLIC SECTOR BANK EMPLOYEES - Kumar, Gajinder; Geetanjali, Dr (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Employees of public sector banks in Haryana, India, are the target of this study, which seeks to understand both the origins and consequences of stress in this demographic. Using an exploratory and descriptive mixed-methods research strategy, this study aims to identify stress patterns, identify workplace characteristics that contribute to stress, and analyze the effects of stress on employee health and organizational performance. 125 workers from several public sector banks in the area made up the research’s representative sample. A researcher-administered structured questionnaire with both open-ended and Likert-scale items was used to collect data. This was done to guarantee that the responses were clear and accurate. To supplement and enhance the analysis, a large amount of secondary data was culled from scholarly journals, books, government publications, official bank websites, and previous research studies. High workload, unclear roles, lack of management assistance, and pressure to fulfill targets are major sources of stress for bank staff, according to the study. Reduced job satisfaction, worsening health, decreased productivity, and increased absenteeism are all symptoms of stress. At the end of the study, the authors address the critical requirement of immediate, organization- and person-level actions to reduce stress and foster a stronger, healthier banking workforce. The findings of this study offer important new information for the discussion of workplace health and lay the groundwork for actionable policy suggestions for the public banking sector.